Case Report: Adolescent epididymal cysts: three management approaches including a rare synchronous epididymal cyst and testicular torsion - Xu, Qichao; You, Cancan; Wu, Jianhong; Xia, Qiongzhang; Chen, Congde; Xia, Liguang (Frontiers in Surgery, 2025)
IntroductionEpididymal cysts are common benign lesions that typically present as painless scrotal masses. They predominantly occur in adult males but can also be found in adolescents, albeit with a higher likelihood of being overlooked at this age. Most patients experience relief or complete resolution of symptoms following conservative treatment. However, large cysts pose a risk of torsion. Torsion of an epididymal cyst in adolescents is clinically rare, with only a few reported cases to date, presenting diagnostic challenges for clinicians.Case descriptionsWe report three cases of epididymal cysts in adolescents. Case 1 involved an asymptomatic cyst treated with aspiration, demonstrating significant cyst reduction at 4-month follow-up. Case 2 presented a persistent simple cyst managed by elective surgical excision with pathological confirmation after prolonged surveillance showed no resolution. Case 3 presented acutely with pain and suspected torsion on scrotal ultrasound, requiring emergency surgical intervention that revealed a 720° torsion of the epididymal cyst combined with 180° testicular torsion, treated testis detorsion and cyst excision. All cases achieved favorable outcomes.ConclusionEpididymal cysts in adolescents warrant a tailored management strategy. While aspiration or elective excision are effective for non-acute cases, the potential for synchronous testicular torsion necessitates a high index of suspicion and prompt surgical exploration in acute presentations to preserve testicular viability.